Anti-scaling performances of different aged landfill leachates on PPR and ABS pipe materials. (11th January 2023) - Zhao, Rui; Chen, Jingfang; Liu, Jie; Li, Min; Yang, Hongwei
Abstract: Landfill leachate, because of its complex components, may cause pipe clogging during its collection and transportation, and pose a threat to the environment. This study considers two typical drainage pipe materials, i.e., polypropylene-random (PPR) and acrylonitrile-butadiene-styrene (ABS), to discriminate their anti-scaling performances through a landfill leachate immersion experiment. The results show that both PPR and ABS pipe materials immersed in the younger-aged leachate are prone to scaling. The mass concentrations of Ca 2+ in the leachate play a key role in scale formation, followed by Mg 2+, pH, oxidation–reduction potential (ORP), dissolved oxygen (DO), and Cl − . In particular, Ca 2+, pH, and DO show a positive relationship in scaling, while Mg 2+ acts in a negative relationship. Calcium carbonate is the major constituent of the scales, accounting for 72.3% of the total. The scaling on the surface of the PPR pipe material is more serious than that of the ABS pipe material, revealed by the corresponding weight increment that is 33% higher than that related to ABS during the experimental period. It is thus indicated that ABS has better anti-scaling performance, which may be an optional material selected for the system design of leachate collection and transportation. HIGHLIGHTS: Two typical drainage pipe materials are discriminated by their anti-scaling performances. Key factors regarding leachate water quality that may give rise to scaling are identified. Ca 2+ plays a dominant role in scale formation. Younger-aged leachate is more prone to scaling than older-aged leachate. ABS has better anti-scaling performance than PPR.